Contrasting seasonal patterns in particle aggregation and dissolved organic matter transformation in a sub-Arctic fjord - M. G. Digernes; Y. V. Bodur; M. Amargant-Arumí; O. Müller; J. A. Hawkes; S. G. Kohler; U. Dietrich; M. Reigstad; M. L. Paulsen (Biogeosciences)
Particulate (POM) and dissolved (DOM) organic matter in the ocean are important components of the Earth's biogeochemical cycle. The two are in a constant state of dynamic change as a result of physical and biochemical processes; however, they are mostly treated as two distinct entities, separated operationally by a filter. We studied the seasonal transition of DOM and POM pools and their drivers in a sub-Arctic fjord by means of monthly environmental sampling and by performing experiments at selected time points. For the experiments, surface water (5 m) was either pre-filtered through a GF/F filter (0.7 µm) or left unfiltered, followed by 36 h incubations. Before and after incubation, samples were collected for dissolved and particulate organic carbon concentrations (DOC, POC), extracellular polymeric substances (EPSs), microbial community (flow cytometry), and molecular composition of DOM (high-performance liquid chromatography coupled to high-resolution mass spectrometry – HPLC-HRMS). During the biologically productive period, when environmental POC concentrations were high (April, June, September), the filtered water showed an increase in POC concentrations. While POC concentrations increased in September, DOM lability decreased based on changes in the average hydrogen saturation and aromaticity of DOM molecules. In contrast, during the winter period (December and February), when environmental POC concentrations were low, lower concentrations of POC were measured at the end of the experiments compared to at the start. The change in POC concentrations was significantly different between the biologically productive period and the winter period (t test; p<0.05). Simultaneously, the DOM pool became more labile during the incubation period, as indicated by changes in the average hydrogen saturation, aromaticity, and oxygen saturation, with implications for carbon cycling. The change in POC was not directly associated with an antagonistic change in DOC concentrations, highlighting the complexity of organic matter transformations, making the dynamics between POC and DOC difficult to quantify. However, in both periods, bacterial activity and EPS concentrations increased throughout the incubations, showing that bacterial degradation and physical DOM aggregation drive the transformations of POM and DOM in concert but at varying degrees under different environmental conditions.